Seroprevalence of Japanese encephalitis virus using competitive enzyme linked immunosorbent assay (C-ELISA) in pigs in East Sumba, Indonesia (Journal of Advanced Veterinary and Animal Research, 2015)
Japanese  Encephalitis  (JE),  a  vector-borne  zoonotic viral disease, is mostly prevalent in Asian countries. The  objective  of  this  study  was  to  investigate  the occurence  of  JE  virus  (JEV)  among  pigs  in  East Sumba,  Indonesia.  Blood  samples  (n=52)  were randomly  collected  from  52  apparantly  healthy  pigs where  pig  population  was  high  in  East  Sumba.  The samples were subjected for seroprevalence  study for the  presence  of  antibodies  against  JEV  using competitive enzyme linked immunosorbent assay (C-ELISA).  Results  showed  that  53%  (n=28/52)  blood samples  from  the  pigs  contained  antibodies  against JEV.  This  finding  is  suggestive  that  the  JEV  is circulating  among  pig  population  in  East  Sumba, Indonesia.  The  data  may  help  in  designing  control strategies of the JEV in the East Sumba, Indonesia. http://dx.doi.org/10.5455/javar.2015.b112